Factors That Influence The Purchasing Power Of Generation Z Consumers Buying Thrifting Clothes (Special Study: In Week 18, Binjai City) - Alyara Oktika Ginting; Rahmad Sembiring; Ahmad Fadlan (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the factors influencing the purchasing power of Generation Z consumers in buying thrift clothing at Pekan 18, Binjai City. The thrifting phenomenon has increased significantly among Generation Z along with the development of social media, environmental awareness, and lifestyle changes toward sustainable fashion. This research uses a quantitative approach with a survey method by distributing questionnaires to 109 Generation Z respondents in Binjai Timur District, Sumber Karya Village. The data analysis techniques used are Confirmatory Factor Analysis (CFA) to reduce variables and multiple linear regression to examine the partial and simultaneous effects of independent variables on consumer purchasing power. The independent variables include price, product quality, lifestyle, brand image, social media influence, environmental awareness, and store image. The results are expected to show that simultaneously all independent variables influence Generation Z purchasing power, with one variable being the most dominant factor. This study is expected to contribute to thrift business actors in formulating marketing strategies and to local governments in supporting creative economy development and environmental sustainability.